Therapeutic Values of Earthworm Species Extract from Azad Kashmir as Anticoagulant, Antibacterial, and Antioxidant Agents - Rozina Ghulam Mustafa; Andleeb Dr Saiqa; Jorge Domínguez; Madiha Jamil; Saira Manzoor; Samna Wazir; Bushra Shaheen; Asma Parveen; Rida Khan; Shaukat Ali; Nazish Mazhar Ali; Fatima Jalal; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Aims. Current research aimed to explore the therapeutic values of different earthworms as antibacterial, anticoagulant, and antioxidant agents. Methods. Ten different earthworms, i.e., Amynthas corticis, Amynthas gracilis, Pheretima posthuma, Eisenia fetida, Aporrectodea rosea, Allolobophora chlorotica, Aporrectodea trapezoides, Polypheretima elongata, Aporrectodea caliginosa, and Pheretima hawayana, were collected and screened for biological activities. Antibacterial effect analysis of earthworm species was done against fourteen bacterial pathogens, i.e., Escherichia coli, Serratia marcescens, Streptococcus pyogenes, Staphylococcus epidermidis, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa (1), Salmonella typhimurium, Shigella flexneri, Enterobacter amnigenus, Serratia odorifera, Pseudomonas aeruginosa (2), Staphylococcus warneri, and Lactobacillus curvatus, via agar well diffusion, crystal violet, MTT, agar disc diffusion, and direct bioautography assays. Antioxidant potential was evaluated through ABTS and DPPH assays. Lipolytic, proteolytic, and amylolytic assays were done for lipase, protease, and amylase enzymes confirmation. In vitro anticoagulant effects were examined in the blood samples by measuring prothrombin time. Results. Results revealed that all earthworm extracts showed the inhibition of all tested bacterial pathogens except P. aeruginosa (1), P. aeruginosa (2), S. warneri, and L. curvatus. The maximum zone of inhibition of E. coli was recorded as 14.66 ± 0.57 mm by A. corticis, 25.0 ± 0.0 mm by P. posthuma, 20.0 ± 0.0 mm by E. fetida, and 20.0 ± 0.0 mm by A. trapezoid. Cell proliferation, biofilm inhibition, the synergistic effect of extracts along with antibiotics, and direct bioautography supported the results of agar well diffusion assay. Similarly, P. hawayana, A. corticis, A. caliginosa, and A. trapezoids increase the prothrombin time more efficiently compared to other earthworms. A. corticis, A. gracilis, A. rosea, A. chlorotica, P. elongata, and A. trapezoides showed maximum DPPH scavenging potential effect. Conclusions. The coelomic fluid of earthworms possessed several bioactive compounds/enzymes/antioxidants that play an important role in the bacterial inhibition and act as anticoagulant agents. Therefore, the development of new therapeutic drugs from invertebrates could be effective and potential for the prevention of the emergence of multidrug-resistant bacteria.